THE EFFECT OF USING PROJECT BASED LEARNING MODEL WITH AUTOPLAY MEDIA STUDIO ON LEARNING ACHIEVEMENT - Harahap, Hasda Nami; Ritonga, Asnil Aidah (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
The purpose of this research was to test the use of the Project-Based Learning (PjBL) model with AutoPlay Media Studio 8. Using a quantitative quasi-experimental design with a nonequivalent control group design. The sampling technique used was nonprobability sampling with purposive sampling. Data were collected by administering pre-test, post-test, and questionnaires. The average pre-test scores of both groups were relatively similar, with the experimental group scoring 50,53 and control group scoring 52,00. The average post-test score of the experimental group was 93,47, higher than the control group’s score of 84,21. The hypothesis testing resulted in a tvalue of 4,340 and a ttable value of 2,028, with a significance level (α) of 0,05. Since the calculated tvalue was greater than the ttabel value was less than o,o5, the full hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The findings of this research indicated that the use of the PjBL model with AutoPlay Media Studio 8 was effective in teaching Islamic Education. Furthemore, the N-Gain test showed that the experimental group achieved a high criterion score of 87,4269, while the control group achieved a moderate criterion score of 66,5780. This suggested that students have improved their understanding of the taught material. The use of the PjBL model with the development of AutoPlay Media Studio 8 as a learning tool will create an interactive and impactful learning experience for Islamic Education at SMP IT Al-Hijrah.